Laser Therapy in Dermatology: Hopes or Hype? - Mahmud, Md Mostaque (Bangladesh Journal of Medicine, 2023)
Laser therapy is a newly adopted surgical option in Dermatology. Targeted photo-thermolysis with minimal injury to the surrounding tissue is the principle of laser therapy. It became popular in affluent society for its aesthetic use. Regarding rejuvenation, pigmented lesions, and unwanted hair removal laser therapy is superior to other available options. Laser therapy is an excellent option for vascular lesions like hemangioma, telangiectasia, and port wine stain. The most commonly used laser is CO2laser. It can be used to ablate growth and resurface scars and wrinkles. The advantages of laser therapy over conventional surgery are less chance of bleeding, scarring, and infections. Laser therapy is a unique option for tattoo removal. In many dermatological diseases, laser therapy shows some glimpses of light where other options failed. In every aspect laser therapy is a modern smart way to treat skin problems. But it is costly and not reachable to common people. There is a false belief in patients that lasers can cure all skin diseases. Practically a minor portion of skin diseases can be managed by laser therapy. Only laser cannot change your skin according to your expectation rather you need filler, botulinum toxin, chemical peel, medications, and sometimes plastic surgery along with laser therapy. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 193